2002
DOI: 10.1080/1354850021000015285
|View full text |Cite
|
Sign up to set email alerts
|

The willingness of women to participate in a long-term trial of hormone replacement therapy: A qualitative study using focus groups

Abstract: The actual proportion of eligible people who participate in clinical trials is low. Consequently, a qualitative study of the willingness of women who are postmenopausal to participate in a long-term randomized control trial of hormone replacement therapy (HRT) designed to investigate the prevention of degenerative diseases was conducted. Focus group methodology was employed to explore the personal and social aspects of decision making about trial participation. Participants were randomly selected from the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…In the study by Searight & Miller [14], patients often emphasised taking part in clinical trials as performing a valuable service to the community of sufferers to which they belonged. However, studies exploring motivations for taking part in medical research, including trials, have found that patients are also driven by reasons of self-interest, seeing it as a means of ensuring treatment by a specialist or securing the best available therapies and medical care [6-13,15,16,26]. Schutta and Burnett [18] note that in their investigation, patients expressed surprise that people would participate in clinical trials for altruistic reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Searight & Miller [14], patients often emphasised taking part in clinical trials as performing a valuable service to the community of sufferers to which they belonged. However, studies exploring motivations for taking part in medical research, including trials, have found that patients are also driven by reasons of self-interest, seeing it as a means of ensuring treatment by a specialist or securing the best available therapies and medical care [6-13,15,16,26]. Schutta and Burnett [18] note that in their investigation, patients expressed surprise that people would participate in clinical trials for altruistic reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Potential barriers to participation in clinical trials have been identified as: unwillingness to accept the possibility of clinical uncertainty and equipoise [4,20,25]; unwillingness to accept the idea of treatment allocation at random [4-6,17,19,23], the possibility of being randomised to placebo rather than active treatment [13,21,23] and holding clear preferences for a particular method of management [26]; worry about receiving 'experimental' treatments [6] or being used as 'guinea pigs' [8,24]; reluctance to change treatment [7]; the belief that trial participants might be denied access to new treatments or that the trial did not offer the best available treatment [21,23] and the view that any benefits of taking part would not outweigh the risks [15,21,24,26]. Distrust of the medical profession and lack of knowledge of what is required of trial participants have also been highlighted as potential barriers [22]; as has inconvenience and discomfort [2,12] and fear of side-effects [7,26].…”
Section: Introductionmentioning
confidence: 99%
“…The questions focused on four main areas: [1] practical barriers to participation, [2] types of research design, [3] motivation to join research, and [4] the conduct of recruitment and research at the centre. The interviews were fully transcribed and independently read several times by researchers.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The study aimed to explore the perspectives of users of a cancer care centre in Edinburgh, Scotland, on research participation in relation to four questions [1]. What practical barriers, if any, are there to participation?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation